Phenotypic variability in bioprocessing conditions can be tracked on the basis of on‐line flow cytometry and fits to a scaling law. Issue 8 (24th July 2015) - Baert, Jonathan; Kinet, Romain; Brognaux, Alison; Delepierre, Anissa; Telek, Samuel; Sørensen, Søren J.; Riber, Leise; Fickers, Patrick; Delvigne, Frank
Abstract Noise in gene and protein expression is a major cause for bioprocess deviation. However, this phenomenon has been only scarcely considered in real bioprocessing conditions. In this work, a scaling‐law derived from genome‐scale studies based on GFP reporter systems has been calibrated to an on‐line flow cytometry device, allowing thus to get an insight at the level of promoter activity and associated noise during a whole microbial culture carried out in bioreactor. We show that most of the GFP reporter systems investigated and thus corresponding genes could be included inside the area covered by the scaling‐law. The experimental results suggest that this scaling‐law could be used to predict the dynamics of promoter activity, as well as the associated noise, in bioprocessing conditions. The knowledge acquired throughout this work could be used for the design of more robust expression systems.